Effect of Body Weight Supported Treadmill Training on Motor Function of Rats with Spinal Cord Injury Based on AMPK-Autophagy Signaling Pathway - CAI Jili; ZHAI Chenyuan; WANG Zun; WU Qi; FANG Lu; WANG Yu; WANG Tong (康复学报)
ObjectiveTo explore the effect and mechanism of body weight supported treadmill training on motor function of rats with spinal cord injured (SCI) based on the adenosine monophosphate-activated protein kinase (AMPK)-autophagy signaling pathway.MethodsA total of 30 10-week-old female SD rats were randomly divided into sham operation group, model group, and exercise group, with 10 cases in each group. Allen's method was used to establish T10 incomplete spinal cord injury models in the model group and the exercise group, while the sham operation group only underwent sham operation. All the three groups received preconditioning exercise training for 3 days before SCI modeling to adapt to the treadmill environment. From the 8th day after modeling, the exercise group received treadmill training with weight reduction of 20%-40% of the body mass, and the treadmill speed was set at 6 m a minute, 20 minutes a time, twice a day for 3 weeks. The sham operation group and the model group were allowed to move freely without treadmill training after modeling. Basso-Beattie-Bresnahan (BBB) method was used to assess motor function of hind limbs of rats at the 1st, 7th, 14th, 21st and 28th days after modeling. Gait analysis system was used to assess gait parameters (footprint area, stride length, touchdown intensity, swing speed and movement speed) after intervention (at the 28th day after SCI). Nissl staining was used to observe the morphology and count of spinal cord neurons. Western blot method was used to detect the protein expression levels of p-AMPK, t-AMPK, LC3 and p62 in spinal cord tissue.Results(1) BBB score: compared with the sham operation group, the BBB score of the model group and the exercise group were significantly lower at the 1st, 7th, 14th, 21st and 28th days after modeling (P<0.05). Compared with the model group at the same time, the BBB score of the exercise group was significantly higher at the 14th, 21st and 28th days after modeling, and the differences were statistically significant (P<0.05). The BBB score in the model group and the exercise group were compared at different times, and the differences were statistically significant (P<0.05). (2) Gait parameters: compared with the sham operation group, the footprint area, touchdown intensity, swing speed, stride length and movement speed were significantly lower in the model group, and the footprint area was significantly lower of the exercise group (P<0.05); compared with the model group, the footprint area, touchdown intensity, swing speed, stride length and movement speed were significantly higher in the exercise group at the 28th day after modeling, and the differences were statistically significant (P<0.05). (3) Morphology and number of neurons in the anterior horn of the spinal cord: compared with the sham operation group, the number of neurons in the anterior horn of the spinal cord reduced significantly in the model group (P<0.05), and nuclear pyknosis was observed. Compared with the model group, Nissl bodies were more clearly observed in the exercise group, nuclear pyknosis reduced significantly, and the number of surviving neurons in the anterior horn of the spinal cord increased significantly (P<0.05). (4) Protein expression levels of p-AMPK, t-AMPK, LC3, and p62: compared with the sham operation group, LC3 Ⅱ/LC3 Ⅰ decreased significantly in the model group, and p62 increased significantly (P<0.05). Compared with the model group, LC3 Ⅱ/LC3 Ⅰ and p-AMPK/t-AMPK increased significantly in the exercise group, and p62 decreased significantly (P<0.05).ConclusionBody weight supported treadmill training can improve the neurological function and hindlimb motor function of rats with SCI, which may be related to the activation of the spinal AMPK-autophagy signaling pathway.